2015
DOI: 10.1146/annurev-pathol-012414-040438
|View full text |Cite
|
Sign up to set email alerts
|

Protein Glycosylation in Cancer

Abstract: Neoplastic transformation results in a wide variety of cellular alterations that impact the growth, survival, and general behavior of affected tissue. Although genetic alterations underpin the development of neoplastic disease, epigenetic changes can exert an equally significant effect on neoplastic transformation. Among neoplasia-associated epigenetic alterations, changes in cellular glycosylation have recently received attention as a key component of neoplastic progression. Alterations in glycosylation appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
613
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 693 publications
(625 citation statements)
references
References 277 publications
(240 reference statements)
8
613
0
4
Order By: Relevance
“…Although the amount and type of carbohydrate chains are inconceivably huge, the type of elementary carbohydrate residues constituting diverse carbohydrate‐chains is fortunately limited, especially these in mammalian cells. Based on the core structures of N‐linked and O‐linked oligosaccharides,13 the common monosaccharide residues are the following ones:13 N‐acetyl‐D‐glucosamine (GlcNAc), N‐acetylgalactosamine (GalNAc), fucose (Fuc), mannose (Man), galactose (Gal), and sialic acid (Sia). Moreover, based on our related studies on carbohydrates6,14, 15, 16 we found the carbohydrates tended to form clusters as functional domains, where various functional glycocongujates locate via being cross‐linked by carbohydrate‐binding proteins (CBPs), with the contributions of lipid rafts as the stable factors and actin cytoskeletion as restricted factors.…”
Section: Introductionmentioning
confidence: 99%
“…Although the amount and type of carbohydrate chains are inconceivably huge, the type of elementary carbohydrate residues constituting diverse carbohydrate‐chains is fortunately limited, especially these in mammalian cells. Based on the core structures of N‐linked and O‐linked oligosaccharides,13 the common monosaccharide residues are the following ones:13 N‐acetyl‐D‐glucosamine (GlcNAc), N‐acetylgalactosamine (GalNAc), fucose (Fuc), mannose (Man), galactose (Gal), and sialic acid (Sia). Moreover, based on our related studies on carbohydrates6,14, 15, 16 we found the carbohydrates tended to form clusters as functional domains, where various functional glycocongujates locate via being cross‐linked by carbohydrate‐binding proteins (CBPs), with the contributions of lipid rafts as the stable factors and actin cytoskeletion as restricted factors.…”
Section: Introductionmentioning
confidence: 99%
“…One such change typically seen in tumors is the alteration of protein glycosylation (1). In particular, changes in mucin-type O-linked glycosylation have been associated with cancer development and poor prognosis-and many diagnostic markers are based on these changes (1).…”
mentioning
confidence: 99%
“…One such change typically seen in tumors is the alteration of protein glycosylation (1). In particular, changes in mucin-type O-linked glycosylation have been associated with cancer development and poor prognosis-and many diagnostic markers are based on these changes (1). Mucin-type O-linked glycosylation is initiated by a family of enzymes (known as the GalNAcTs 3 or ppGalNAcTs) that catalyze the addition of GalNAc onto the serine or threonine residues of proteins transiting the Golgi apparatus (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, aberrant glycosylation is directly linked with many human diseases (4). Of note, glycans serve as useful biomarkers of various cancers and targets of therapeutic intervention (4)(5)(6)(7). Glycan binding proteins (GBPs) read the diversity and complexity of glycans in a relatively specific manner and execute the physiological or pathological information encoded by the polymers (1,8).…”
mentioning
confidence: 99%